Phase synchrony in slow cortical potentials is decreased in both expert and trained novice meditators. (14th May 2019) - Jo, Han-Gue; Naranjo, Jose Raul; Hinterberger, Thilo; Winter, Ulf; Schmidt, Stefan
Highlights: SCP phase synchrony was examined during resting state and mindfulness mediation. Expert meditators exhibited reduced synchronization during meditation. The same result was found in novices after an 8-week meditation practice. Abstract: Neuronal interactions coupled by phase synchronization have been studied in a wide range of frequency bands, but fluctuations below the delta frequency have often been neglected. In the present study, phase synchrony in slow cortical potentials (SCPs, 0.01–0.1 Hz) was examined during two different mental states; a resting state and a breath-focused mindfulness meditation. SCP phase synchrony in 9 long-term expert meditators (on average 22 years of experience) were compared with the data obtained from 11 novices. Additionally, after the novices attended an 8-week mindfulness-based stress reduction (MBSR) program, SCP phase synchrony was measured again. While expert meditators and novices exhibited the same amount of SCP phase synchrony in the resting state, decreased synchronization was found during meditation among expert meditators as well as novices who had participated in the MBSR program (but not prior to the program). These findings suggest that phase synchrony in slow cortical activity is context-dependent and could provide crucial information in the study of the human mind.